Investigation of the Physical Mechanisms of the Formation and Evolution of Equatorial Plasma Bubbles During a Moderate Storm on 17 September 2021 - Kun Wu; Liying Qian; Wenbin Wang; Xuguang Cai; Joseph M. Mclnerney (Space Weather)
Abstract We investigate in detail the occurrence and evolution of ionospheric equatorial plasma bubbles (EPBs) during a moderate storm on 17 September 2021, using Global‐scale Observations of the Limb and Disk (GOLD) observations and Whole Atmosphere Community Climate Model‐eXtended (WACCM‐X) simulations. GOLD observations show that there were no EPBs on 16 September before the storm but EPBs occurred after the storm commencement on 17 September. The EPBs extended to ∼30° magnetic latitude. A diagnostic analysis of WACCM‐X simulations reveals that the rapid enhancement of prompt penetration electric fields (PPEFs) after the sudden storm commencement is the main reason that triggered the occurrence of the EPBs. Further quantitative analysis shows that vertical plasma drifts, which are enhanced by the PPEF, played a dominant role in strengthening the Rayleigh‐Taylor instability, leading to the occurrence of the EPBs and the large latitudinal extension of the EPBs to ∼30° magnetic latitude during the night of 17 September.